Strategy For Forming A Sustainable Society In The New Uzbekistan - Avazov Kоmil (Global Scientific Publishing, 2024)
The formation of a threat-resistant society is a complex process, and various models, forms of management and methods of its organization and management have been developed. The strategy for creating a threat-resistant society in New Uzbekistan is analyzed by the author from a socio-political point of view.
Keywords: transition period; adaptation; modernization